Titles of TV Programmes in Finnish Newspapers: a Context for Proverbs in Contemporary Use. - Granbom-Herranen Liisa (University of Bialystok, 2022)
The article focuses on the everyday use of proverbs, concentrating on proverbs in two Finnish newspapers and using some of the results of the previous cooperative paremiologic project. The study highlighted some special cases in the use of proverbs in Finnish daily newspapers as the fairly rich use of proverbs in the titles and sub-headings of TV programmes. This article focuses on proverb use in ti-tles, studying it as a culture-bound phenomenon. The article combines two phenom-ena originating from different eras and living conditions. On the one hand, Finnish proverbs originate from an oral agrarian context and often use old-fashioned, agrar-ian language and concepts, but in contemporary use they exist in a new context. The television, however, is a relatively new phenomenon; it has been more than just a pure technological innovation. The article’s perspective is based in folkloristic paremiology.
Reproducible language units from an interdisciplinary perspective